1987
DOI: 10.1136/pgmj.63.739.373
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella intracerebral and subdural abscess--report of two cases

Abstract: Summary:Two cases of the rarely encountered SalmoneUla typhi subdural empyema are reported. The first was in an 11 month old infant and the second in a 25 year old adult. Neither of them suffered from typhoid fever. The causative organism was not suspected until the culture report was obtained. Both patients responded satisfactorily to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Only about 80 cases of focal intracranial infections have been reported [1], which includes our 6 cases. Among these are 22 brain abscesses, 40 subdural empyemas and another 18 cases with combinations of two or more pathologies, mostly as case reports [1, 2, 4, 7, 8, 9, 11, 13, 14, 15, 16, 17, 18, 19]. No large series of subdural empyema due to Salmonella infection has been reported in the literature, which highlights the rarity and paucity of the literature on this entity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Only about 80 cases of focal intracranial infections have been reported [1], which includes our 6 cases. Among these are 22 brain abscesses, 40 subdural empyemas and another 18 cases with combinations of two or more pathologies, mostly as case reports [1, 2, 4, 7, 8, 9, 11, 13, 14, 15, 16, 17, 18, 19]. No large series of subdural empyema due to Salmonella infection has been reported in the literature, which highlights the rarity and paucity of the literature on this entity.…”
Section: Discussionmentioning
confidence: 94%
“…The infections are in the form of meningitis, subdural effusions and empyemas [4, 7, 8, 11, 12, 13, 14, 15, 16, 17], extradural empyema [1, 5, 6, 17], brain abscess and cerebral venous infarcts. Rarely, there can be association of more than one pathology [2, 4, 9, 11]. In a 100-year review of focal Salmonella intracranial infections, Rodriguez et al [5]in 1986 highlighted the rarity of this condition and added one case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,12,13 In a series of 30 cases, Renier et al 7 reported meningitis in 20 patients and septicemia in 13. In rare cases brain abscess can be a complication of cyanotic heart disease, compound head injury and ventriculoperitoneal shunts in children.…”
Section: Discussionmentioning
confidence: 99%
“…Common organisms in neonatal meningitis and brain abscess are reported to be Proteus mirabilis and Serratia marcescens. 6,7,[12][13][14][15][16][17] In rare cases, enterococci have also been isolated from the pus of neonatal brain abscesses. 12,18 Staphylococcal meningitis or brain abscess in neonates or infants is a rarity and is by and large secondary to a dermal sinus.…”
Section: Discussionmentioning
confidence: 99%